Tetramethylpyrazine nitrone improves motor dysfunction and pathological manifestations by activating the PGC-1α/Nrf2/HO-1 pathway in ALS mice. (January 2021) - Wen, Jing; Li, Shangming; Zheng, Chengyou; Wang, Fengjiao; Luo, Yangwen; Wu, Liangmiao; Cao, Jie; Guo, Baojian; Yu, Pei; Zhang, Gaoxiao; Li, Shupeng; Sun, Yewei; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive loss of upper and lower motor neurons that results in skeletal muscle atrophy, weakness and paralysis. Oxidative stress plays a key role in the pathogenesis of ALS, including familial forms of the disease arising from mutation of the gene coding for superoxide dismutase (SOD1). We have used the SOD1 G93A ALS mouse model to investigate the efficacy of 2-[[(1, 1-dimethylethyl)oxidoimino]-methyl]-3, 5, 6-trimethylpyrazine (TBN), a novel tetramethylpyrazine derivative armed with a powerful free-radical scavenging nitrone moiety. TBN was administered to mice by intraperitoneal or intragastric injection after the onset of motor deficits. TBN slowed the progression of motor neuron disease as evidenced by improved motor performance, reduced spinal motor neuron loss and the associated glial response, and decreased skeletal muscle fiber denervation and fibrosis. TBN treatment activated mitochondrial antioxidant activity through the PGC-1α/Nrf2/HO-1 pathway and decreased the expression of human SOD1. These findings suggest that TBN holds promise as a therapeutic agent for ALS. Highlights: TBN effectively improves motor functions of SOD1 G93A mice. TBN significantly attenuates muscular pathologic changes in SOD1 G93A mice. TBN obviously reduces the expression of human SOD1 in SOD1 G93A mice. TBN validly decreases MDA and ROS levels in the serum of SOD1 G93A mice. TBN significantly increases PGC-1α, Nrf2, HO-1 protein expression in SOD1 G93A mice.